Four weeks of probiotic supplementation reduces GI symptoms during a marathon race - Pugh, J. N.; Sparks, A. S.; Doran, D. A.; Fleming, S. C.; Langan-Evans, C.; Kirk, B.; Fearn, R.; Morton, J. P.; Close, G. L. (European Journal of Applied Physiology, 2019)
Purpose: To evaluate the effects of probiotic supplementation on gastrointestinal (GI) symptoms, circulatory markers of GI permeability, damage, and markers of immune response during a marathon race. Methods: Twenty-four recreational runners were randomly assigned to either supplement with a probiotic (PRO) capsule [25 billion CFU Lactobacillus acidophilus (CUL60 and CUL21), Bifidobacterium bifidum (CUL20), and Bifidobacterium animalis subs p. Lactis (CUL34)] or placebo (PLC) for 28 days prior to a marathon race. GI symptoms were recorded during the supplement period and during the race. Serum lactulose:rhamnose ratio, and plasma intestinal-fatty acid binding protein, sCD14, and cytokines were measured pre- and post-races. Results: Prevalence of moderate GI symptoms reported were lower during the third and fourth weeks of the supplement period compared to the first and second weeks in PRO (p < 0.05) but not PLC (p > 0.05). During the marathon, GI symptom severity during the final third was significantly lower in PRO compared to PLC (p = 0.010). The lower symptom severity was associated with a significant difference in reduction of average speed from the first to the last third of the race between PLC (- 14.2 ± 5.8%) and PRO (- 7.9 ± 7.5%) (p = 0.04), although there was no difference in finish times between groups (p > 0.05). Circulatory measures increased to a similar extent between PRO and PLC (p > 0.05). Conclusion: Probiotics supplementation was associated with a lower incidence and severity of GI symptoms in marathon runners, although the exact mechanisms are yet to be elucidated. Reducing GI symptoms during marathon running may help maintain running pace during the latter stages of racing.